2015
DOI: 10.1111/age.12347
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of the GBP1 gene as a candidate gene for porcine reproductive and respiratory syndrome resistance

Abstract: A genomic region in pig chromosome 4 has been previously associated with higher viraemia levels and lower weight gain following porcine reproduction and respiratory syndrome virus (PRRSV) infection. The region includes the marker WUR1000125, a G>A polymorphism next to a putative polyadenylation site in the 3'-untranslated region (3'-UTR) of the guanylate-binding protein 1, interferon-induced (GBP1) gene. The protein encoded by GBP1 is a negative regulator of T-cell responses. We show here that GBP1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Since the role of posttranscriptional modification has gradually gained attention, more and more studies have also focused on the polyadenylation of single gene in pig [46][47][48]. Many methods based on NGS technology currently emerged as the times require, including poly(A) site sequencing…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the role of posttranscriptional modification has gradually gained attention, more and more studies have also focused on the polyadenylation of single gene in pig [46][47][48]. Many methods based on NGS technology currently emerged as the times require, including poly(A) site sequencing…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we took the simultaneous existence of genes that are associated with tissue-specific PASs above and the predicted differential target genes of miRNA and RBPs. Some shared genes were discovered to be involved in muscle fiber transformation, such as HDAC (47)(48)(49), TRIB3 (50), and GYS1 [45].…”
Section: Annotation Of Mirnas and Rbps To Detect Possiblementioning
confidence: 99%
“…) and the association of GBP1 with respiratory and reproductive syndrome resistance (Gol et al . ). Previous research has also shown that the myosin, heavy chain 4, skeletal muscle gene ( MYH4 ) in Landrace pigs may be a potential molecular marker related to meat quality traits (Cho et al .…”
Section: Introductionmentioning
confidence: 97%
“…The porcine GBP1 gene is a negative regulator of the T-cell response, the gene expression of which might be associated with viremia levels and lower weight gain following porcine reproduction and respiratory syndrome virus (PRRSV)22. Recently, Gol et al .…”
mentioning
confidence: 99%
“…Interestingly, different alleles of the mutation affected the usage of two PASs in 3′UTR of GBP1 gene. The distal PAS is more commonly used in all test samples, and the short transcript is generated by the proximal PAS when the A allele is present22. The study suggested that the APA participates in the formation of different lengths of transcripts and results in various expressions for GBP1 .…”
mentioning
confidence: 99%